Insider Trading, Option Exercises and Private Benefits of Control - Peter Cziraki; Peter de Goeij; Luc Renneboog (Hungarian Academy of Sciences, Institute of Economics, 2010)
We investigate patterns of abnormal stock performance around insider trades and option exercises on the Dutch market. Listed firms in the Netherlands have a long tradition of employing many anti-shareholder mechanisms limiting shareholders rights. Our results imply that insider transactions are more profitable at firms where shareholder rights are not restricted by antishareholder mechanisms. This finding goes against the monitoring hypothesis which states that more shareholder orientation and stronger blockholders would reduce the gains from insider trading. We show robust support for the substitution hypothesis as insiders of firms which effectively curtail shareholder rights enjoy valuable private benefits of control in lieu of engaging in insider trading to exploit their position.
Keywords: G14; G34; M52; 330; insider trading; management stock options; timing by insiders; corporate governance; antishareholder mechanisms; anti-takeover mechanisms; Insiderhandel; Aktienoption; Corporate Governance; Shareholder Value; Niederlande